Daya Hambat In Vitro Ekstrak Buah Bintaro (Cerbera manghas L.) terhadap Jamur Penyebab Busuk Akar (Ganoderma sp.) pada Kelapa Sawit - Fradilla Swandi; Febrianti Febrianti; Salmiyati Salmiyati; Dewi Andri Yani (Universitas Respati Indonesia, 2025)
Ganoderma sp. is a fungal pathogen that causes basal stem rot in oil palm, leading to production losses of up to 80%. One potential method to inhibit fungal growth is the use of plant-based fungicides derived from bintaro fruit (Cerbera manghas L.) extract. This study aims to determine the effective concentration of C. manghas fruit extract for controlling Ganoderma sp., the causal agent of basal stem rot disease in oil palm, under in vitro conditions. The extract was tested at concentrations of 0%, 4%, 6%, 8%, and 10% using a Completely Randomized Design with five treatments and five replications. The extract was prepared using distilled water (simple extraction) and incorporated into PDA medium. Observed parameters included fungal colony area, mycelial dry weight, and mycelial fresh weight. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level. The results indicated that C. manghas fruit extract inhibited the growth of Ganoderma sp. The 6% extract concentration exhibited the highest inhibitory effect, reducing colony area by 15.49%, dry weight by 31.30%, and fresh weight by 30.77%.